SEMANTIC CLASSIFICATION OF POLITICAL LEXICON: ARCHAISMS, NEOLOGISMS, HISTORICISMS - Ismatova Shakhnoza Akhror's daughter (American Journals Publishing, 2023)
In this article, opinions were expressed about the semantic classification of political lexicon.
Keywords: strategy, political, meaning, semantics, archaisms, neologisms, historicisms